2020
DOI: 10.1007/s00038-020-01460-w
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic differences in factors associated with alcohol use among adolescents in Slovenia: a cross-sectional study

Abstract: Objectives. This paper aims to investigate the association of parental, friends, and personal factors with the risk of alcohol use in a sample of Slovenian adolescents, and whether these associations differ by socio-economic status of the school area (SES). Methods. The survey involved 2946 students of 44 Slovenian primary schools in the school year 2010/2011. The association between sociodemographic characteristics, parental alcohol use and permissiveness to drink, parental monitoring, perception of friends' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…McCartney et al (2016) found that the changes in income, social, and demographic factors has affected the rate of death caused by alcohol consumption. Social factor also were the predictors of alcohol consumption in the study of Mehanović et al (2020) in Slovenia where the findings indicate that parent alcohol consumption, low monitoring, peer, belief, and refusal skills are important factors for alcohol consumption.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…McCartney et al (2016) found that the changes in income, social, and demographic factors has affected the rate of death caused by alcohol consumption. Social factor also were the predictors of alcohol consumption in the study of Mehanović et al (2020) in Slovenia where the findings indicate that parent alcohol consumption, low monitoring, peer, belief, and refusal skills are important factors for alcohol consumption.…”
Section: Resultsmentioning
confidence: 88%
“…Social factors have an important effect on alcohol consumption. (Ajan & Hanafiah Juni, 2016;Beard et al, 2019;Collins, 2016;Huckle et al, 2018;Juliana Gabrielle et al, 2016;Mehanović et al, 2020;Moan & Halkjelsvik, 2020;Sadler et al, 2017;Stafström & Agardh, 2013;Stapinski et al, 2016;Thern & Landberg, 2020) Socioeconomic factors…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…The 28 articles identified on parental alcohol intake only (i.e., not specifying children's observation of alcohol use) linked greater frequency and/or volume of consumption to negative alcohol‐related outcomes for their children [46, 79, 80, 83–107]. This effect was observed across numerous countries and cultural contexts, including Australia [87], Brazil [85, 90], Chile [86], China [105], Germany [97], Ireland [98], Japan [88], Mexico [107], Slovenia [96], Spain [101], Taiwan [79], the United Kingdom [91, 93, 94] and the United States [89, 92].…”
Section: Resultsmentioning
confidence: 99%
“…The 28 articles identified on parental alcohol intake only (i.e., not specifying children's observation of alcohol use) linked greater frequency and/or volume of consumption to negative alcohol‐related outcomes for their children [46, 79, 80, 83–107]. This effect was observed across numerous countries and cultural contexts, including Australia [87], Brazil [85, 90], Chile [86], China [105], Germany [97], Ireland [98], Japan [88], Mexico [107], Slovenia [96], Spain [101], Taiwan [79], the United Kingdom [91, 93, 94] and the United States [89, 92]. Thirteen of the identified studies were longitudinal and found that parental alcohol use is associated with children subsequently engaging in underage alcohol consumption, suggesting a causal link between these two outcomes [79, 84, 87, 90–94, 97, 99, 101, 103, 104].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation